New challenges to democratization - Burnell, Peter J.; Youngs, Richard, 1968- (London : Routledge, 2010)
'This important text explores the widespread contention that new challenges and obstacles have arisen to democratization, assessing the claim that support for democratization around the world is facing a serious challenge. Bringing together leading international scholars of democratization, including Thomas Carothers, Michael McFaul, Laurence Whitehead, Bassma Kodmani, Nancy Bermeo, Marina Ottaway, Shaun Breslin and,Renske Doorenspleet, this book examines the issues relating to developments within non-democratic states and issues related to the democratic world and its efforts to support the spread of democracy. Featuring in-depth studies on the limits of US democracy promotion, the Middle East, Russia, China and new democracies, the book sheds light on such questions as: Is the wave of democratization now in retreat or should we be careful not to exaggerate the importance of recent setbacks? Do serious, sustainable alternatives to democracy now exist? Is international democracy promotion finished? New Challenges to Democratization brings together a variety of academics and writers from major think-tanks in the United States and Europe, and makes the book ideally suited to a wide international readership. This book will be of particular interest to students and scholars of democratization, comparative politics and international politics'--Back cover.
New challenges to democratization / Peter Burnell -- State sovereignty and democracy : an awkward coupling / Laurence Whitehead -- Ideological challenges to democracy : do they exist? / Marina Ottaway -- The continuing backlash against democracy promotion / Thomas Carothers -- Democracy assistance and the search for security / Nancy Bermeo -- Public support versus dissatisfaction in new democracies : an'inside challenge'? / Renske Doorenspleet -- External sources and consequences of Russia's'sovereign democracy' / Michael Mcfaul and Regine A Spector -- Democratizing one-party rule in China / Shaun Breslin -- Democratization by whom? Resistance to democracy promotion in the Middle East / Bassma Kodmani -- Energy : a reinforced obstacle to democratization? / Richard Youngs -- Addressing democracy's challenges / Peter Burnell and Richard Youngs.
Includes bibliographical references (p. [201]-215) and index.
Mode of access : World Wide Web.
Keywords: Democratization; Democracy; Electronic books